Problematika Berbahasa di Era Digital: Antara Disrupsi Teknologi dan Erosi Struktur Bahasa: Language Problems in the Digital Era: Between Technological Disruption and Erosion of Language Structure - Chamdar Nur; Baso Pallawagau (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The digital revolution marked by the rise of the internet, social media, and artificial intelligence has fundamentally transformed human communication, including language use. This study examines linguistic problems in the digital era through the lenses of sociolinguistics and media linguistics, focusing on how technological disruption affects language structure, function, and etiquette. The main objectives are to analyze forms of linguistic degradation (grammar, vocabulary, and ethical use), evaluate the impact of platform algorithms and modalities on register shifts, and identify signs of the erosion of standard language. A qualitative-descriptive method was employed, including literature review, discourse observation in digital spaces, and semiotic analysis of communication practices on social media and messaging apps. The findings reveal a significant shift from formal language structures to more instant, flexible, and multimodal forms; phenomena such as word shortening, emojis, and code-switching reflect the dominance of practicality over structural preservation. This research contributes by providing a scientific basis for language-based digital literacy policies, the development of adaptive language learning curricula, and the affirmation of the urgency to preserve the national language amid digital flows. It enriches the discourse of digital sociolinguistics as an emerging discipline in contemporary language studies.